MEANS OF DEVELOPMENT OF THE SYSTEM OF SOCIAL RESPONSIBILITY AT THE MICRO-LEVEL OF MANAGEMENT - MITSENKO, Nataliia; HRADYUK, Nataliia; BODNARIUK, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The purpose of the article is the scientific substantiation of the theoretical, methodological and applied aspects of ensuring the development of social responsibility at the micro-level of management, which involves modelling the influence of factors on the social capital of this level. Тhe priority role of social responsibility in establishing and ensuring the development of entrepreneurial activity is substantiated. A number of scientific statements regarding the essence and features of social responsibility at the micro-level of management are summarized. The list of means of stimulating the social responsibility of the enterprise is grouped. The importance of implementing basic standards of social responsibility at enterprises was emphasized. A methodological approach has been modified and proposed, which allows you to verify the values of the indicators, which are used mostly at the stages of evaluating the efficiency of the enterprise. The list of factors determining the possibility of increasing or decreasing the social capital of the enterprise is summarized. It is proved that the mathematical interpretation of the importance of the influence of each factor on the possibilities of social capital change is the determination of weighting coefficients, which is carried out in several stages. It is emphasized that thanks to social responsibility, it is possible to increase the rate of growth of the efficiency of the use of resources at the micro-level of management. It has been proven that changes in social capital are essential for achieving a certain degree of enterprise management efficiency, which determines the compliance of its capabilities with regard to meeting new social, household, material and other needs directly of the staff, as well as market participants (buyers, business partners, certain groups of society). At the same time, the dynamics of social capital are influenced by factors that create the possibility of the emergence and development of social relations and ensure their preservation. It was concluded that the development of social responsibility of the enterprise increasingly determines its success in the competitive environment, increased business activity, and increased influence on the market.